Análisis didáctico de los libros de vacaciones de 5º curso de Educación Primaria / Analysis of holiday books from 5th grade Primary Education - Carmen Morales Menayo (Tejuelo: Didáctica de la Lengua y la Literatura)
The summer provides parents of our students the opportunity to acquire the books that publishers offer to the children review the knowledge acquired during the course. All publishers offer this type of material, hence the interest in analyzing from the legislative, educational and pedagogical books the holiday five different publishers view. In this article the importance of these books is justified and pursued through analysis of its structure and the types of activities that present current frame and authors of major psychological and pedagogical theories.